Factors Influencing Job Satisfaction at Pt.Bersama Cipta Mandiri Karawang - Abdul Rozak; Doni Apri Irawan; Santi Pertiwi Hari Sandi; Dwi Epty Hidayaty (Journal of Finance and Business Digital, 2023)
This observation activity was carried out at PT.Bersama Cipta Mandiri Karawang which is a company engaged in the food sector, this observation was carried out with the aim of knowing the factors that influence employee job satisfaction at PT.Bersama Cipta Mandiri. The method used is descriptive observation by means of interviews and taking pictures. The population of this research is all employees of PT. Together with Cipta Mandiri, totaling 10 people. the method used is by way of direct interviews. The result of this observation is that the work environment has a significant effect on job satisfaction and comfort at PT. Together with Cipta Mandiri Karawang by 70%, and work factors have no significant effect on job satisfaction at PT. Together with Cipta Mandiri Karawang with a significant level of 30%.